Clinical case of Gradenigo syndrome, difficulties of differential diagnosis - Elena S. Ananyeva; Marina V. Popova; Olga B. Laricheva (LLC "MEDIAFORMAT", 2023)
Gradenigo syndrome develops with pathology of the apex of the temporal bone pyramid. This syndrome is characterized by a clinical lesion of the vestibulocochlear nerve in combination with dysfunction of the abducens, trigeminal and facial nerves. The rarity of occurrence of the syndrome, the lack of experience of doctors working with patient with this pathology, the small namber of publications in Russian scientific journals on the diagnosis and treatment of diseases in the area of the apex of the temporal bone lead to the lack of timely diagnosis and adequate treatment of diseases that cause syndrome. The article describes a clinical case of a patient with Gradenigo syndrome, which developed as a result of pathology of the apex of the temporal bone and associated with a neoplasm, which was subsequently determined to be a poorly differentiated carcinoma with squamous cell differentiation of the skull base.